Influence of placental exosomes from early onset preeclampsia women umbilical cord plasma on human umbilical vein endothelial cells - Gu, Mengqi; Zhang, Fengyuan; Jiang, Xiaotong; Chen, Pengzheng; Wan, Shuting; Lv, Qingfeng; Lu, Yuan; Zhou, Qian; Wang, Yanyun; Li, Lei (Frontiers in Cardiovascular Medicine, 2022)
Background Early onset preeclampsia (EOSP, PE) is characterized by hypertension, proteinuria, and endothelial dysfunction. Oxidative stress-induced trophoblast dysfunction is a major pathology in PE. Placental exosomes are extracellular vesicles that are involved in “mother-placenta-foetal communication” and can regulate the biological functions of endothelial cells. Our study was designed to evaluate placental exosomes effects on endothelial cells. Methods Umbilical cord blood from normal pregnant women and patients with PE were collected. A hypoxia/reoxygenation (H/R) model in human first trimester extravillous trophoblast cell (HTR8/SVneo) line to simulate the PE model of oxidative stress in vitro. Then, placental exosomes (i.e., NO-exo, H/R-exo, N-exo, and PE-exo) were extracted and identified. Finally, the effects of placental exosomes on the biological functions of human umbilical vein endothelial cells (HUVECs) were further evaluated by performing a series of experiments. Results Placental exosomes had a double-membrane cup structure with diameters of 30–150 nm, and there was no obvious difference in placental exosomes. Compared with NO-exo and N-exo, H/R-exo and PE-exo inhibited HUVECs proliferation, tube formation and migration, increased permeability and apoptosis in vitro. Conclusion We hypothesize that H/R-exo and PE-exo impair vessel development by disrupted biological functions in endothelial cells, which may result in vascular disorders in offspring.